2020
DOI: 10.2196/14414
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Health Information and Their Impacts on Medical Knowledge Perception Among the Saudi Arabian Population: Cross-Sectional Study

Abstract: Background Having a reliable source for health information is vital to build a strong foundation of knowledge, especially with the current revolution of the internet and social media, which raises many concerns regarding harmful effects on the health of the public. However, there are no studies on how the Saudi Arabian population seeks health information. Details about the most used and trusted sources of health information among the public will help health authorities and public awareness accounts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 17 publications
6
49
1
1
Order By: Relevance
“…These findings highlight the need for COVID-19 vaccine messaging to be mainly communicated by health officials and health care providers through the KSA MoH and Government. HCWs also play a crucial role in being one of the most trusted sources of medical information for the general public in the KSA ( Alduraywish et al, 2020 ). As the KSA MoH begins to vaccinate its general population ( Ministry of Health, 2021 ), it must immediately address any COVID-19 vaccine misinformation among the HCW population to achieve a high vaccination rate among the public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the need for COVID-19 vaccine messaging to be mainly communicated by health officials and health care providers through the KSA MoH and Government. HCWs also play a crucial role in being one of the most trusted sources of medical information for the general public in the KSA ( Alduraywish et al, 2020 ). As the KSA MoH begins to vaccinate its general population ( Ministry of Health, 2021 ), it must immediately address any COVID-19 vaccine misinformation among the HCW population to achieve a high vaccination rate among the public.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a survey sent to the KSA general population found that most KSA adults reported false information about the COVID-19 pandemic and vaccines (e.g., flu and pneumonia vaccines protect against COVID-19) ( Baig et al, 2020 ). Given that misinformation can have serious implications on worsening the spread of the virus and potentially reducing vaccine acceptance, HCWs play an important role in being a source of trusted medical information for the KSA general public ( Alduraywish et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many people consider the Internet to be a useful and important source of health information [6][7][8][9] that can encourage the use of preventive strategies and consultation with physicians [10]. On March 13, 2020, Google Trends reported that the term "coronavirus" was searched five million times (supplemental appendix), underlining the importance of the Internet as a source for health information.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Information on such a widely discussed topic will inevitably be vast and vary in production quality, potentially adversely affecting patient awareness and health-seeking behaviour. 4 Many of these resources read by the public may be unreliable or produced from non-peer-reviewed sources and affect behaviours such as recognition of symptoms, taking appropriate preventative precautions or seeking timely treatment. 3 5 6 Furthermore, inaccurate online information may contradict healthcare professionals and potentially compromise the trusting relationship with patients worsening outcomes.…”
Section: Introductionmentioning
confidence: 99%